Competition, Complementarity and Increasing Disparities Among the Regions of Spain and Portugal - Sandy Dall'erba (European Regional Science Association (ERSA), 2003)
The aim of this paper is to investigate the competitive or complementary relationships between the regions of Spain and Portugal over the last two decades. Competitive and complementary dynamics between their regions relies on their intense trade, based on their comparative advantages or disadvantages in conjunction with the influence of increasing or decreasing returns and lowered transaction costs. Our analysis is based on the application of the Dendrinos-Sonis model (1988, 1990) to the Gross Domestic Regional Product of the regions of Spain and Portugal and covers the 1977-2000 period. Essentially, the analysis implies that growth in regional income is similar to a zero-sum game in which the growth in one region takes place at the expenses of a least one another. It is formalized in a log-linear discrete relative interaction function and estimated using a seemingly unrelated estimator. Since Spain and Portugal are among the poorest members of the European Union, the second part of the paper extends the application to the four key sectors of regional development policies: agriculture, energy, transportation and non-market services. The complementary or competitive relationships that are revealed raise important issues on the nature of spillover effects between regions. The results contribute also to the debate efficiency versus equity in the spatial and sectoral distribution of European regional development funds. References Dendrinos D. and Sonis M. (1988), Nonlinear Discrete Relative Population Dynamics of the U.S. Regions, Applied Mathematics and Computation, 25, 265-285. Dendrinos D. and Sonis M. (1990), Chaos and Socio-Spatial Dynamics. Applied Mathematical Scences 86. Springer, Heidelberg.
Keywords: 330